DYNAMIC ANALYSIS OF PIPELINES BY MEANS OF NORMAL MODE SHAPES TAKING INTO ACCOUNT INTERACTION WITH THE ENVIRONMENT - Дубик, Я. Р. (Science-based technologies, 2016)
The orthogonality conditions of the eigenfunctions or mode shape for the fluid-structure interaction problem is presented. The exact orthogonality conditions are derived, for junction and Poisson coupling. The example of the numerical analysis of classic water hammer in the pipeline due to the sudden valve closure is presented. It is shown that the coupled fluid-structure interaction analysis gives more accurate results in the calculation of pressure surges and displacements.